Nematodes and their bacterial prey improve phosphorus acquisition by wheat. Issue 3 (2nd December 2022) - Jiang, Ying; Wang, Zhonghua; Liu, Ye; Han, Yanlai; Wang, Yi; Wang, Qiang; Liu, Ting
Summary: Plant growth is greatly influenced by the rhizosphere microbiome, which has been traditionally investigated from a bottom‐up perspective assessing how resources such as root exudates stimulate microbial growth and drive microbiome assembly. However, the importance of predation as top‐down force on the soil microbiome remains largely underestimated. Here, we planted wheat both in natural and in sterilized soils inoculated with the key microbiome predators – bacterivorous nematodes – to assess how plant performance responds to top‐down predation of the soil microbiome and specific plant growth‐promoting bacteria, namely phosphate‐solubilizing bacteria. We found that nematodes enriched certain groups (e.g. Actinobacteria, Chloroflexi, and Firmicutes) and strengthened microbial connectance (e.g. Actinobacteria and Proteobacteria). These changes in microbiome structure were associated with phosphate‐solubilizing bacteria that facilitated phosphorus (P) cycling, leading to greater P uptake and biomass of wheat in both soils. However, the enhancement varied between nematode species, which may be attributed to the divergence of feeding behavior, as nematodes with weaker grazing intensity supported greater abundance of phosphate‐solubilizing bacteria and better plant performance compared with nematodes with greater grazing intensity. These results confirmed the ecological importance of soil nematodes for ecosystem functions via microbial co‐occurrence networks and suggested that the predation strength of nematodes determines the soil bacteria contribution to P biogeochemical cycling and plant growth.